THE EFFECT OF PROBLEM BASED LEARNING MODEL TO THE LEARNING OUTCOMES OF CLASS X SEMESTER II ON THE SUBJECT MATTER TEMPERATURE AND HEAT IN STATE HIGH SCHOOL 1 OF HAMPARAN PERAK T.P. 2016/2017 - Sri Siska Rahmayani; Juniar Hutahean (Universitas Negeri Medan, 2017)
Abstract.This research aims to determine the effect of problem based learning to the results of class X student second semester in the subject matter of temperature and heat in state high school 1 Hamparan Perak T.P.2016/2017. This type of research is quasi experiment. The study population was all class X state high school 1 Hamparan Perak. Samples were taken at random cluster sampling technique, which is a class X MIA 5 as the experimental class using problem-based learning model, and class X MIA 4 as the control class using direct learning model. The research instrument is as much as 7 about the test description. Data were analyzed using t-test two parties and one party t test. Results showed the average value pretest experimental classes and control classes are 30,08 and 29,94. The average value for both classes postes 75,34 and 66,86. Both classes have a variation in normal distribution and homogeneous. The test results test two parties obtained t <t table (0,12 <1,99) demonstrated the ability of the same early in the second grade. The test results of the t test obtained t> t table (3,48> 1,66) showed no significant effect of problem based learning to the results of class X student second semester in the subject matter of temperature and heat in state high school 1 Hamparan Perak T.P.2016/2017.